VOX : sittmöbel för det offentliga rummet - Wallmark, Anders (SLU/Dept. of Urban and Rural Development, 2010)
A trend in modern landscape architecture is to design pedestrian streets so that vehicles and people move in the same area. By doing this, traffic tends to slow down. On the market though, there is a lack of furniture that corresponds to the requirements of these kinds of public places. Therefore, I have designed this furniture, called VOX, which is planned to be used on streets, schoolyards and squares. One objective has been to promote the product to the industry.